Designing and utilizing 3D-printed skin incision guides during the first Dutch bilateral hand-arm transplantation. Issue 11 (November 2021) - Hummelink, S.; Kruit, A.S.; Hovius, S.E.R.; Ulrich, D.J.O.
Summary: Objective: To preoperatively plan skin incision in the case of the first Dutch bilateral hand-arm transplantation. Background: A bilateral hand-arm transplantation has been performed for the first time in the Netherlands in 2019. In the context of preparation for this surgical procedure, the optimal patient-specific skin flap was determined. Skin flaps should be properly matched between donor and recipient to ensure sufficient tissue for the approximation of skin over the tendon anastomosis, adequate distal tip perfusion, and esthetics. Methods: Preoperatively, stereophotogrammetry was obtained from the upper extremities of the patient and a volunteer with similar body physique. Skin flap dimensions were determined for each extremity, which resulted in patient-specific incision patterns. Combining this digital information yielded practical skin incision guides for both the donor and acceptor arms. Finally, the computer-aided designs were 3D printed. Results: The 3D prints were convenient to utilize in both shaping the donor flaps as in preparing the acceptor extremities, taking only a few seconds during precious ischemia time. There was sufficient skin flap perfusion, and the wound-healing followed an uncomplicated course. No corrections were made to the initial skin incisions. Conclusions: Three-dimensional printed templates were successfully utilized in the first Dutch bilateral hand-arm transplantation. We believe its usage increased time efficiency, improved the match of skin flaps in donor and recipient arms, and allowed us to control the amount of skin surplus without skin flap tip necrosis. In these procedures where time is of the essence, we believe preoperative planning is imperative for its success.